“The making of Europe“
1 online resource.
Keywords: In “The Making of Europe”: Essays in Honour of Robert Bartlett , a group of distinguished contributors analyse processes of conquest, colonization and cultural change in Europe in the tenth to fourteenth centuries. They assess and develop theses presented by Robert Bartlett in his famous book of that name. The geographical scope extends from Iceland to the Islamic Mediterranean, from Spain to Poland. Themes covered range from law to salt production, from aristocratic culture in the Christian West to Islamic views of Christendom. Like the volume that it honours, the present book extends our understanding of both medieval and present day Europe. Contributors are Sverre Bagge, Piotr Górecki, John Hudson, Hugh Kennedy, Simon MacLean, William Ian Miller, Esther Pascua Echegaray, Ana Rodriguez, Matthew Strickland, John Tolan, Bjorn Weiler, and Stephen D. White. This is an excellent collection of essays that do justice to Rob Bartlett’s inexhaustible book, The Making of Europe . Rather than merely repeating and venerating Bartlett’s ideas, the essays engage creatively and critically with them and spark new ideas and insights that cast a flood of light on the culture of medieval Europe. The result is a worthy tribute that will send readers scurrying back to Bartlett to quarry yet more nuggets from The Making of Europe , still fizzing with intellectual brio some twenty years after its publication. Stuart Airlie, University of Glasgow October 2015